2023
DOI: 10.1149/1945-7111/acb66c
|View full text |Cite
|
Sign up to set email alerts
|

Review—Research Progress and Prospects of Li-Air Battery in Wearable Devices

Abstract: Li-air batteries have high theoretical energy density, making them a powerful candidate for flexible electrical products power supply. However, there are many challenges to commercializing Li-air battery in wearable devices, such as the problem of H2O and CO2 gas pollution and electrolyte volatilization caused by open structure. In addition, the construction of high efficiency flexible cathode, effective protection of anode materials, and the suppression of Li dendrites, and reasonable temperature control meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…34 Our paper reporting on the discovery of Li-air battery in the Journal Electrochemical Society received more than two thousand citations, and it helped initiate worldwide research and development of the Li-air battery which is still in full force. 38 We have also found that a Magnesium/Oxygen battery could be constructed with a Mg ion conducting polymer electrolyte of the composition, 30PVdF-HFP-62.5 EC/PC-7.5Mg(ClO4)2 where PVdF-HFP is poly(vinylidene fluoride)-hexafluoropropene with a conductivity of 1.2 × 10 −3 S cm −1 at 20 °C. This Mg/O 2 cell showed an open circuit potential of ∼1.2 V at room temperature, lower than the calculated value of 2.93 V, and its discharge voltage ranged between 0.7 to 1.1 V depending on the state of charge.…”
Section: Practical Rechargeable LI Batteriesmentioning
confidence: 83%
“…34 Our paper reporting on the discovery of Li-air battery in the Journal Electrochemical Society received more than two thousand citations, and it helped initiate worldwide research and development of the Li-air battery which is still in full force. 38 We have also found that a Magnesium/Oxygen battery could be constructed with a Mg ion conducting polymer electrolyte of the composition, 30PVdF-HFP-62.5 EC/PC-7.5Mg(ClO4)2 where PVdF-HFP is poly(vinylidene fluoride)-hexafluoropropene with a conductivity of 1.2 × 10 −3 S cm −1 at 20 °C. This Mg/O 2 cell showed an open circuit potential of ∼1.2 V at room temperature, lower than the calculated value of 2.93 V, and its discharge voltage ranged between 0.7 to 1.1 V depending on the state of charge.…”
Section: Practical Rechargeable LI Batteriesmentioning
confidence: 83%
“…have been developed. [200][201][202] Great attention has been paid in the development of such batteries because of their enhanced theoretical capacity as well as their low cost. Vacancy engineering played a vital role on the improvement in battery performance for various electrode materials, including metal oxides/mixed metal oxides, sulphides, hydroxides, etc.…”
Section: Secondary Batteriesmentioning
confidence: 99%
“…Lithium metal, as a highly reactive metal, possesses a high reduction potential and low oxidation potential, resulting in a higher theoretical voltage and theoretical energy density in Liair batteries. [41][42][43] However, due to its high reactivity, lithium is unsuitable for operation in high-temperature and highhumidity environments. In contrast, Zn-air batteries (ZABs), utilizing the less reactive zinc metal, offer a lower theoretical voltage and energy density but are more adaptable to hightemperature and humid conditions.…”
Section: Mab Structure and Principlementioning
confidence: 99%